Perpindahan Kalor pada Penukar Kalor Selongsong dan Pipa Memakai Sekat Miring Tidak Sejajar - Nadjib, Muhammad (Jurnal Semesta Teknika, 2012)
Generally speaking, baffle installation of a shell-and-tube heat exchanger is in straight-standing with respect to shell axis. A common problem of this arrangement is that there will be found a stagnant fluid condition in the death-zone. The impact is the heat transfer coefficient could not reach an optimum value. Based on baffle configuration, the death-zone effect can be minimized by installing an un-parallel tilted baffle. The purpose of this research is to investigate the effect of using non-parallel tilted baffle on heat transfer coefficient. The heat exchanger model was made with single pass fluids. Hot water is going through inside the tube bundles and cold water pass is in the shell. The baffle was installed in various angle of 0°, 15°, 30°, and 45° with respect to shell axis. The cold water flow rates were varied from 75 l/hr, 100 l/hr, 125 l/hr, 150 l/hr, 175 l/hr, to 200 l/hr. The hot water flow rate was fixed at 150 l/hr. Temperature of the hot and cold water at inlet and outlet was recorded by means of K type thermocouple and data logger. The data was then analyzed to obtain the convection heat transfer coefficient. The data were also used to determine the empirical correlation of Nusselt number and Reynolds number. The results indicate that baffle in angle 0° produce the highest convection heat transfer coefficient. Installing the baffle at tilted position is not significant in convection heat transfer coefficient. The empirical correlation of Nusselt number and Reynolds number is influenced by angle function of the baffle.